(untitled) (Journal of Industrial and Mechanical Engineering, 2020)
The use of natural resources has become indiscriminate due to various factors, among which the population increase stands out and, therefore, the increase in consumption associated with it. This represents an imminent challenge for humanity, which must achieve development that preserves these resources to satisfy current needs without harming the needs of future societies. This work aims to develop a documentary analysis methodology to show the role of organizations and the State in the challenge. For this reason, it is considered essential to understand what tools an organization must achieve sustainability and what public policies the State can determine to guide development. This study covers Argentina and will in turn provide an idea of articulation between these two protagonists.